The Application of Zakat On Business Results As A Strategic Effort To Build The Economy of The People of Medan City - Aulia, Nurul; Tanjung, Dhiauddin; Matsum, Hasan (Journal of Law, Politic and Humanities, 2024)
This study aims to assess the essence of zakat on business results as an instrument in improving the welfare of the community and describe the implementation of zakat on business results as a strategic effort in building the economy of the people of Medan city. This research uses descriptive qualitative method to provide as much detail as possible about the implementation of business zakat. This research is a normative-empirical research with the research subjects of businesses in Medan city whose profits have reached nisab and haul. The object of this research is business zakat based on the Qur'an and hadith. The data collection technique used in this research is by collecting data from related literature such as the Qur'an, journals, books and other sources that support this research, then using reading and recording techniques. Data analysis techniques using descriptive techniques. The results of this study show: (1) Definition of Zakat on Business Results; (2) Businesses in Medan City that can be charged with Zakat on Business Results; (3) Application of Zakat on Business Results in the View of Islamic Law.